Distinct Factors Secreted by Adipose Stromal Cells Protect the Endothelium From Barrier Dysfunction and Apoptosis - Lu, Hongyan; Merfeld-Clauss, Stephanie; Jawed, Yameena; March, Keith L.; Coleman, Michael E.; Bogatcheva, Natalia V. (Frontiers in Cell and Developmental Biology, 2020)
We have shown previously that adipose stromal cell (ASC)-derived conditioned media (CM) limited lung injury, endothelial barrier dysfunction, and apoptosis. Here, we used endothelial hyperpermeability and apoptosis assays to investigate how concentration processes affect endothelium-directed bioactivity of ASC-CM and to gain information on the nature of bioactive factors. Comparison of ASC-CM concentrated with differential molecular weight (MW) cutoff filters showed that endothelial barrier protection depended on the species-specific factors in ASC-CM fractionated with MW > 50 kDa. Known barrier regulators—keratin growth factor (KGF), vascular endothelial growth factor (VEGF), and hepatocyte growth factor (HGF)—were detected in ASC-CM fraction of > 100 kDa. Pretreatment of endothelial monolayers with concentrations of KGF, VEGF, and HGF detected in ASC-CM showed that only KGF and HGF protect the endothelium from barrier dysfunction. Depletion of KGF and HGF from ASC-CM attenuated ASC-CM’s ability to protect the endothelial barrier. In contrast to barrier-protective factors, apoptosis-protective factors fractionated with MW < 3 kDa and were not species-specific. Application of donors of apoptosis-mitigating gases showed that the CO donor carbon monoxide-releasing molecule 2 (CORM2) protected the endothelium from apoptosis, while the H2S donor NaSH did not. Knockdown of CO-generating heme oxygenase 1 in ASC attenuated ASC-CM’s ability to protect the endothelium from apoptosis. We have shown that tumor necrosis factor alpha (TNFα)-induced apoptosis in endothelium is c-Jun N-terminal kinase (JNK)-dependent, and JNK activation is inhibited by ASC-CM pretreatment of endothelial cells. ASC-CM from heme oxygenase 1-depleted ASC displayed attenuated ability to suppress endothelial JNK activation, suggesting that CO-mediated protection of the endothelium from apoptosis is achieved by the downregulation of the JNK pathway. Altogether, our results demonstrate that the concentration of ASC-CM with low MW cutoff filters significantly reduces its anti-apoptotic activity while preserving its barrier-protective activity.